SISTEM MONITORING KETINGGIAN OMBAK AIR LAUT SECARA REAL-TIME BERBASIS IoT - Dedi Apriadi; Toibah Umi Kalsum; Hendri Alamsyah (UNIVED Press, 2023)
Indonesia is an archipelagic country where most of its territory is water, so all activities carried out in water, especially the sea, are an important part of the life of the Indonesian people. The height of the sea waves is a phenomenon that greatly affects the efficiency and safety of people when they are in sea waters. The process of obtaining sea wave height data requires an appropriate system. So this study designed a prototype system for monitoring the height of sea waves in real-time based on IoT. The method used is the waterfall, where the ultrasonic sensor will be connected to the ESP-8266 nodemcu so that real-time sea wave height data is obtained through the user interface on the Thinger IO Platform. In addition, the system uses red, yellow, and green LEDs as indicators of the height of the water waves. These results indicate that the application of real-time IoT-based sea wave height systems has good capabilities. This is indicated by the user being able to see real-time monitoring data on sea wave height based on IoT with the display of numbers, graphs, and LED indicator lights. For the seawater level scale used in the system, the LED indicator lights in red are 0-10 cm,yellow are 11-20 cm, and green are 21-30 cm.